Smokers’ Treatment Expectancies Predict Smoking Cessation Success - Fucito, Lisa M. (J Smok Cessat, 2014)
INTRODUCTION: Smokers’ treatment expectancies may influence their choice of a particular medication as well as their medication experience. AIMS: This study examined the role of smokers’ treatment expectancies to their smoking cessation outcomes in a completed, randomized, placebo-controlled trial of naltrexone for smoking cessation, controlling for perceptions of treatment assignment. METHODS: Treatment seeking cigarette smokers (N = 315) were randomized to receive either naltrexone (50 mg) or placebo in combination with nicotine patch and behavioral counseling. Expectancies for naltrexone as a smoking cessation aid were assessed at baseline and 4 weeks after the quit date. RESULTS: More positive baseline medication expectancies predicted higher quit rates at one month in the naltrexone (OR =1.45, p =.04) group but were associated with lower quit rates in the placebo group (OR =.66, p =.03). Maintaining and/or increasing positive medication expectancies in the first month of treatment was associated with better pill adherence during this interval in the naltrexone group (ps <.05). Positive baseline medication expectancies were also associated with the perception of having received naltrexone over placebo among all participants. CONCLUSIONS: Positive medication expectancies in smokers may contribute to better treatment response. Assessing treatment expectancies and attempting to maintain or improve them may be important for the delivery, evaluation, and targeting of smoking cessation treatments.